2011
DOI: 10.1080/01140671.2011.577079
|View full text |Cite
|
Sign up to set email alerts
|

Chickpea (Cicer arietinumL.) response to zinc, boron and molybdenum application under field conditions

Abstract: In Spain*Europe's leading chickpea producing country*chickpea (Cicer arietinum) is mainly cultivated on non-irrigated soils with low native fertility. This study was carried out from 2006 to 2008 in the province of Leo´n, Spain, under acid soil field conditions, with the aim of determining whether the application of zinc (Zn), boron (B) and molybdenum (Mo) improved chickpea growth and yield on acid soils. A split-split-plot design with three replications was used. Chickpea responded only to the Zn and Mo appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 26 publications
5
10
0
Order By: Relevance
“…Our results on fruit water content are in agreement with those of Boertje (1969) and with those of Valenciano et al (2011) and Randal (1969) who found that a Mo implementation caused a significantly increase of dry matter production in chickpea and grain, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Our results on fruit water content are in agreement with those of Boertje (1969) and with those of Valenciano et al (2011) and Randal (1969) who found that a Mo implementation caused a significantly increase of dry matter production in chickpea and grain, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The best results would therefore be achieved if micronutrients are applied in conjunction with macronutrients to favorably influence the plant vigor, morphology, and metabolic processes. The results of this experiment are in agreement with the findings of a number of previous research endeavors involving other crops [38,[40][41][42][43]. Yang et al [44] for instance, reported that the combined application of B with Mo or Zn resulted in higher seed yield than the application of B, Mo, or Zn alone, and the combined application of B, Mo, and Zn increased the seed yield by 68.1% compared to the controls.…”
Section: Seed Yieldsupporting
confidence: 91%
“…Micronutrients also increase the number of branches due to the formation of stamens and pollens [36]. The enhancing effect of zinc, boron, and molybdenum on pods per plant has been reported in mungbean [37], chickpea [38], green gram [39], french bean [40], and cowpea [15]. The results of this study contribute to the growing body of knowledge about the effect of these micronutrients on lentils.…”
Section: Number Of Pods Plant −1mentioning
confidence: 52%
“…Significantly the highest number of pods per plant (28.7 in 1 st year and 33.0 in 2 nd year) and seeds per pod (12.1 in 1 st year and 12.0 in 2 nd year) were recorded from the treatment T 8 and the minimum of both characters were noted in T 1 treatment (Table 4). Valenciano et al (2011) reported that combined application of Zn, B and Mo contributed to get maximum number of pods per plant of chickpea. Every micronutrient donated to obtain higher number of pods per plant.…”
Section: Growth and Yield Attributes Of Mungbeanmentioning
confidence: 99%